Chemical control of peptide material phase transitions. Issue 8 (18th January 2021) - Tan, Junjun; Zhang, Li; Hsieh, Ming-Chien; Goodwin, Jay T.; Grover, Martha A.; Lynn, David G.
Abstract : Substrate initiated assembly of a dynamic chemical network. Abstract : Progressive solute-rich polymer phase transitions provide pathways for achieving ordered supramolecular assemblies. Intrinsically disordered protein domains specifically regulate information in biological networks via conformational ordering. Here we consider a molecular tagging strategy to control ordering transitions in polymeric materials and provide a proof-of-principle minimal peptide phase network captured with a dynamic chemical network.